Corrosion inhibitors for steel in concrete: State-of-the-art report - Söylev, Tayfun Altuğ; Richardson, M. G. (ELSEVIER SCI LTD, THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, OXON, ENGLAND, 2008)
This state-of-the-art report is focused on corrosion inhibitors used in concrete and is based on published studies in the last decade. Emphasis was given to the most commonly used inhibitors such as aminoalcohols (AMAs), calcium nitrites (CN) and sodium monofluorophosphates (MFPs). The report presents information related to (a) basic mechanism study, which gives information about the mechanism of protection provided by inhibitors, (b) effectiveness of inhibitors against corrosion in chloride contaminated and carbonated concrete, which deals with the preventive and curing effect of the inhibitors in different environments, (c) penetrability of the inhibitor, which underlines some difficulties of penetration into concrete for migrating corrosion inhibitors (MCIs), (d) influence on fresh and hardened concrete properties, which compares fresh concrete properties, mechanical performance and durability with and without inhibitor, (e) field trials, which gives the limited data on the long-term performance of the inhibitors in real structures. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: corrosion; concrete; reinforcement; admixture; inhibitor; electrochemical impedance spectroscopy; chloride-induced corrosion; high-performance concrete; hardened cement paste; reinforced-concrete; sodium monofluorophosphate; rebar corrosion; contaminated concrete; carbonated concrete; remedial treatment; korozyon; beton; takviye; karışım; önleyici; elektrokimyasal empedans spektroskopisi; klorür-kaynaklı korozyon; yüksek performanslı beton; sertleştirilmiş çimento hamuru; betonarme; sodyum monoflorofosfat; inşaat demiri korozyon; kirlenmiş beton; gazlı beton; iyileştirici tedavi